Paul Among the Apocalypses? An Evaluation of the 'Apocalyptic Paul' in the Context of Jewish and Christian Apocalyptic Literature - Davies, J. P. (London Bloomsbury Publishing, 2016)
CONTENTS -- Acknowledgments -- Abbreviations -- Chapter 1 -- PERPLEXED BY THE "APOCALYPTIC PAUL"? -- 1. Introduction -- 2. Paul and Apocalyptic in Recent Study -- 3. Prolegomena -- 4. The Structure of This Book -- Chapter 2 -- EPISTEMOLOGY: REVELATION AND WISDOM -- 1. Introduction -- 2. Epistemological Dichotomies in the "Apocalyptic Paul" -- 3. Epistemological Duality in Jewish Apocalyptic Literature -- 4. Epistemological Duality in the Book of Revelation -- 5. Implications for the Epistemology of the "Apocalyptic Paul" -- Chapter 3 -- ESCHATOLOGY: "IRRUPTION" AND HISTORY -- 1. Introduction
2. Eschatological Dichotomies in the "Apocalyptic Paul" -- 3. Eschatological Duality in Jewish Apocalyptic Literature -- 4. Eschatological Duality in the Book of Revelation -- 5. Implications for the Eschatology of the "Apocalyptic Paul" -- Chapter 4 -- COSMOLOGY: HEAVEN AND EARTH -- 1. Introduction -- 2. Cosmological Dichotomies in the "Apocalyptic Paul" -- 3. Cosmological Duality in Jewish Apocalyptic Literature -- 4. Cosmological Duality in the Book of Revelation -- 5. Implications for the Cosmology of the "Apocalyptic Paul" -- Chapter 5 -- SOTERIOLOGY: DELIVERANCE AND JUSTICE
1. Introduction -- 2. Soteriological Dichotomies in the "Apocalyptic Paul" -- 3. Soteriological Duality in Jewish Apocalyptic Literature -- 4. Soteriological Duality in the Book of Revelation -- 5. Implications for the Soteriology of the "Apocalyptic Paul" -- Chapter 6 -- CONCLUSIONS: QUESTIONING THE DICHOTOMIES -- 1. Aims of This Book -- 2. Apocalyptic Epistemology -- 3. Apocalyptic Eschatology -- 4. Apocalyptic Cosmology -- 5. Apocalyptic Soteriology -- Bibliography -- Index of References -- Index of Authors
Description based upon print version of record
Keywords: Electronic books